Controle fuzzy tolerante a falhas para robôs móveis - Mendes, Luan Vieira (2019)
The problem of fault detection caused by actuators with application to trajectory tracking of wheeled mobile robots (WMRs) is addressed in this thesis. For the considered application, a wheeled mobile robot -having nonlinear kinematics- is required to follow a predefined trajectory in a stipulated time. An environment free of obstacles is used for this task. The goal has to be accomplished despite the presence of faults that may occurr in the actuators of the robot. The proposal presented here uses a Fuzzy Logical Controller to the trajectory tracking problem. For the fault detection problem in the actuators of the WMRs, the states and a loss of effectiveness (LOE) parameter are estimated by a Kalman Filter. The calculated LOE value is used to reconfigure the control signal generated by the Fuzzy Controller guaranteeing the Fault-Tolerant Control (FTC). In the need of a cooperative work for two or more robots with the goal to conclude the trajectory, an algorithm which consider severe faults was developed. The proposed solution grants the aim to be completed by the fault-free robots, leaving those with severes faults behind. Simulations were made in order to validate the proposed solutions. As a main result of the Fault-Tolerant Control, an error of aproximadetely 0,3% of the trajectory goal time was reached